(untitled) (Research, Society and Development, 2021)
Objetive: Characterize what has been produced about risk factors for suicidal ideation, suicide attempt or suicide in the adolescent. Method: Narrative literature review about risk factors for suicidal ideation, suicide attempt or suicide in adolescents. The research was carried out from March to July 2020 with the descriptors "Adolescents" [AND] "Suicide" [AND] "Risk factors". Publications of articles made available in full were included, in Portuguese, English and Spanish, with a five-year timeframe. For the bibliographic survey stage Latin American and Caribbean Health Sciences Information bases were used (LILACS), the National Library of Medicine (PubMed) and Scientific Electronic Library Online (SciELO). Totaling 25 articles that make up the body of this research, after applying the inclusion and exclusion criteria. Results: Suicide is multifactorial and is correlated with social aspects, biological and psychological aspects of each adolescent, where issues related to exposure to violence, troubled family relationships, negative life events, social diferences, educational problems, depression and use of legal and illegal drugs act as risk factors for suicide in adolescents. Conclusion: Adolescents are vulnerable to several problems that can weaken their mental health, which added to the negative influence of risk factors of biological origin, economical, psychological and social, act as causative agents that cause the development of suicidal ideas and/or suicide attempts.